Effects of Levilactobacillus brevis TISTR 860 and Lactiplantibacillus plantarum TISTR 951 on physicochemical properties and gamma-aminobutyric acid in fermented rice flour and Kanomjeen noodles - Chittrakhani, Chonnipa (2022)
Kanomjeen, known as Thai traditional fermented rice noodles is normally made from fermented rice flour, which contain important functional ingredient, which is gamma-aminobutyric acid (GABA). In this study, two starter cultures, which were Levilactobacillus brevis TISTR 860 (LB) and Lactiplantibacillus plantarum TISTR 951(LP) were used to ferment rice slurry and the effect of fermentation time, every 6 h from 0 to 30 h on the lactic acid bacteria (LAB) count were determined. The effect of these starter cultures, to the production of gamma-aminobutyric acid (GABA) were also studied. In addition, the physicochemical properties of the fermented rice flour and rice noodles (Kanomjeen) were also determined in terms of pH, color, titrable acidity, pasting properties, and tensile analysis. L. plantarum has previously shown to improve the characteristics of fermented rice flour, however data on use of both LB and LP on the GABA production and their properties of the fermented rice flour and noodles are limited. Both starter cultures were cultured in MRS broth to achieve 108 CFU/mL and used for the fermentation. The initial pH value of rice slurry was adjusted to 4.5 and enriched with 2% monosodium glutamate (MSG) prior to addition of L. brevis TISTR 860 and L. plantarum TISTR 951, respectively in the samples. After fermentation at 30C for 24 h, the samples were dried at 45C for 6 h, ground and sieve to powder and knead into noodle (kanomjeen). Results showed that at different fermentation time (0 to 30 h), the highest yield of lactic acid bacteria was at 9.3 log CFU/g for both LB and LP after 12 h and 18 h of fermentation. GABA content increased significantly (p<0.05) after 24 h as compared to natural fermentation of rice flour, which took six days to obtain GABA at 36 mg/100g. L. plantarum TISTR 951 yielded more lactic acid and dwindled pH better than L. brevis TISTR 860 but yielded less GABA content. Peak viscosity decreased from 4315 RVU to 2927 and 3465 RVU for fermented rice flour with LB and LP, respectively, as fermentation duration was increased. Fermentation also moderated the whiteness of rice flour while increasing its yellowness. Tensile strength of fermented rice noodles had been increased from 9.79 g to 11.38 g and 11.45 g for LB and LP, respectively, while the elasticity of noodles had been developed from 14.06 to 16.86 mm. In conclusion, LB could yielded more in GABA content than LP, presented in the quantity of 21.80 mg/100 g dry basis in 24 h and also presented a non-significant difference in tensile analysis. The reduction of viscosity, whiteness and, slightly rising of yellowness of fermented rice flour were influenced by the fermentation, as well as the tensile strength and elasticity of fermented rice noodles were increased.